Reactive hypoglycaemia during the OGTT after gestational diabetes mellitus: Metabolic implications and evolution. Issue 11 (1st August 2022) - Quansah, Dan Yedu; De Giorgi, Sara; Le Dizes, Olivier; Camponovo, Chiara; Benhalima, Katrien; Cosson, Emmanuel; Puder, Jardena J.
Abstract: Aims: Gestational diabetes (GDM) presents an increased cardio‐metabolic risk and is diagnosed with an oral glucose tolerance test (OGTT). Reactive hypoglycaemia (RH) during the OGTT in pregnancy is associated with adverse outcomes. Although postpartum OGTT after GDM is recommended, the occurrence and implications of RH are unknown. We investigated the prevalence, metabolic implications and longitudinal evolution of RH at 6–8 weeks postpartum in women with a history of GDM. Methods: Between 2011 and 2021, we consecutively followed 1237 women with previous GDM undergoing an OGTT at 6–8 weeks postpartum. RH was defined as 2‐h glucose <3.9 mmoL/L after the OGTT. Metabolic outcomes were compared in women with and without RH (RH+/RH−). We also included a subcohort of 191 women with data on insulin sensitivity/secretion indices (MATSUDA, HOMA‐IR, insulin‐adjusted‐secretion ISSI‐2). Results: The postpartum prevalence of RH was 12%. RH+ women had a more favourable metabolic profile including a 2‐5‐times lower prevalence of glucose intolerance and metabolic syndrome at 6–8 weeks postpartum compared to RH− (all p ≤ 0.034). In the subcohort, women with RH+ had higher insulin sensitivity, higher ISSI‐2 and an earlier glucose peak after OGTT ( p ≤ 0.049) compared to RH− women at the same time point. Insulin resistance increased and ISSI‐2 decreased over the first year postpartum in both groups. These changes were associated with a 50% reduction in overall RH prevalence at 1‐year postpartum. Some of the favourable profiles of RH+ persisted at 1‐year postpartum, without group differences in the longitudinal metabolic changes. Conclusions: At 6–8 weeks postpartum, RH was frequent in women after GDM and associated with a better metabolic profile including increased insulin sensitivity and higher insulin‐adjusted‐secretory capacity. RH might be a marker of favourable metabolic prognosis in women with a history of GDM.